Effect of two weeks of training cessation on concentric and eccentric knee muscle strength in highly trained sprinters - Yamashita, D.; Hirata, K.; Yamazaki, K.; Mujika, I.; Miyamoto, N. (PLOS ONE, 2023)
Athletes often experience short-term training cessation because of injury, illness, post-season vacation, or other reasons. Limited information is available about the effect of short-term (less than four weeks) training cessation on muscle strength in athletes. Sprinting athletes must maintain knee extension and flexion strength to reduce the risk of sprint-type hamstring strain injury. This study aimed to identify whether and to what extent knee extension and flexion torque in concentric and eccentric contractions is reduced by two weeks of training cessation in sprinters. Before and after the training cessation, maximal voluntary isokinetic knee extension and flexion torque in slow and fast concentric (60 and 300°/s) and slow eccentric (60°/s) contractions were assessed in 13 young male highly trained sprinters (average World Athletics points = 978). Knee flexion torque during the bilateral Nordic hamstring exercise (NHE) was also measured. After the training cessation, isokinetic concentric at 300°/s and eccentric torque were significantly reduced in both knee extension and flexion. There was no difference in the magnitude of reduction between isokinetic knee extension and flexion torques in all conditions. The relative changes were more notable in eccentric (-15.0%) than in concentric contraction at 60°/s (-0.7%) and 300°/s (-5.9%). Knee flexion torque during the NHE also declined (-7.9% and -9.9% in the dominant and non-dominant legs, respectively). There was no significant correlation between the relative reductions in isokinetic knee flexion torque and knee flexion torque during the NHE. The findings suggest that sprinters and their coaches should focus on recovering fast concentric and slow eccentric knee extension and flexion strength after two weeks of training cessation.